Main difficulties of the nursing team in acting during the pandemic: an integrative review - Silva, Romário Mateus Oliveira da (2022)
Introduction: The Covid-19 pandemic brought several consequences to society and especially to the health team, because the harmfulness of the disease, the lack of studies on how to act, lack of treatment and vaccination caused the world to collapse. Taking into account this burden on the health system, the role of nurses in coping with the disease is highlighted, as well as the biopsychosocial factors involved in this issue. Objective: To analyze the main challenges listed by nurses during the pandemic period through the chosen bibliography. Materials and methods: This is an integrative review of 10 articles in which nurses were asked about the main challenges faced during this period, and what the main impacts can be seen. Therefore, the analytical method of research was applied, as well as the criterion of time in which the articles analyzed must be published between the years 2020 to 2021, texts in Portuguese and available on free platforms. Results: In the ten articles chosen for analysis, it was shown that nurses face challenges both in the practice of the profession, in the issue of dealing with several deaths in a course of time and combined with the issue of family distancing, several of these professionals have developed diseases of psychological background such as panic attacks, high stress, depression, and all these aspects influence the quality of work of this employee who finds himself overwhelmed during the pandemic. Conclusion: The other diseases do not cease to exist as a result of the pandemic, on the other hand, the pandemic protocols have made nurses feel overloaded and consequently treat all these aspects as difficulties related to the practice of the profession, so it is important to understand the importance of the profession and the challenge of maintaining mental health in this scenario.